Pengembangan Kompetensi Mengajar Mahasiswa Pascasarjana UIN RIL Melalui Pembelajaran Reflektif dalam Pendidikan Islam - Saifullah; Riswandha Ipnu Nawawi; Reski Gunawan; Eni Amaliah; Meriyati (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
This study examines the role of Field study as a reflective learning strategy in developing teaching competence among postgraduate students in Islamic Education Management. Employing a descriptive qualitative approach, the research involved 16 master’s students who conducted face-to-face teaching practice over one academic semester. Data were collected through classroom observations, in-depth interviews, and analysis of teaching videos used in structured Video Review sessions. The findings reveal that the integration of Video Review within the Field study program functions as a critical reflective mechanism that transforms teaching practice into a process of pedagogical self-awareness and professional learning. Beyond improving pedagogical, professional, social, and personal competencies, Video Review enables students to critically evaluate their verbal and non-verbal teaching behaviors, classroom interactions, and instructional decision-making in an objective manner. This reflective process fosters metacognitive awareness, strengthens professional identity, and embeds the Islamic educational value of muhasabah (self-introspection) as a foundation for continuous professional development. This study contributes conceptually by positioning Video Review not merely as an evaluative tool, but as an integral model of reflective learning in Islamic higher education. The findings extend the discourse on reflective teaching by offering a contextualized framework for developing competent, reflective, and value-oriented educators at the postgraduate level of Islamic education.